Problematika Pembelajaran Al-Quran Hadist pada Siswa Kelas X di MAN 1 Ponorogo - Aulia, Mohamad Faisal; Ernawati, Ernawati (Institut Teknologi Pendidikan Indonesia, 2023)
This study aims to determine the problems of learning Al-Quran Hadith in class X students at Man 1 Ponorogo. The method in this study uses a qualitative descriptive research type. The data in this study are in the form of systematic observation and recording of the symptoms that appear on the object of research, as well as interviews with teachers of the Qur'an Hadith subject at class X in Man 1 Ponorogo. The results of the discussion in this study indicate that the problems of learning the Qur'an in Man 1 Ponorogo include weak student abilities, some students cannot read the Qur'an with recitation rules, reading it is still halting and some students still cannot write Arabic. this is due to the heterogeneous background of the students and the lack of parental participation. In addition to the student factor, there is also a lack of learning tools and resources to support Al-Qur'an learning activities. As for the efforts made in overcomingthe problems of learning the Qur'an by holding a tadarus of the Qur'an for all students. In addition, one of the efforts made to overcome the problems of learning the Qur'an is by giving assignments or recommending reading the Qur'an at their respective homes. carry out self-development activities that are carried out regularly every day, provide direction to students and hold Tahfid activities, provide special guidance and motivation so that students are interested in learning without coercion, the most important thing is consistency in learning Al-Qur'an hadith) and holding additional juz 'amma.